Elucidation of the mechanisms into effects of organic acids on soil fertility, cadmium speciation and ecotoxicity in contaminated soil. (January 2020) - Ma, Hang; Li, Xuedan; Wei, Mingyang; Zeng, Guoquan; Hou, Siyu; Li, Dan; Xu, Heng
Abstract: The remediation effect of organic acids in heavy metal contaminated soil was widely studied. However, the comprehensive evaluation of organic acids on micro-ecological environment in heavy metal contaminated soil was less known. Herein, this experiment was conducted to investigate the impact of malic acid, citric acid and oxalic acid on soil fertility, cadmium (Cd) speciation and ecotoxicity in contaminated soil. Especially, to evaluate the ecotoxicity of Cd, high-throughput sequencing was used to investigate the soil bacterial community structure and diversity after incubation with organic acids. The results showed that obvious changes in soil pH were not observed. Whereas, the contents of available phosphorus (Olsen-P) and alkali hydrolysable nitrogen (Alkeline-N) evidently increased with a significant difference. Furthermore, compared to control, the proportion of acetic acid-extractable Cd increased by 3.06–6.63%, 6.11–9.43% and 1.91–6.22% respectively in the groups amended with malic acid, citric acid and oxalic acid, which indicated that citric acid did better in improving the availability of Cd than malic acid and oxalic acid. In terms of biological properties, citric acid did best in bacteria count increase, enzyme activities and bacterial community structure improvement. Accordingly, these results provided a better understanding for the influence of organic acids on the micro-ecological environment in Cd contaminated soil, based on physicochemical and biological analysis. Graphical abstract: Image 1 Highlights: Soil fertility was improved with the addition of organic acids. The availability of Cd could increase with the application of organic acids. Organic acids were effective in soil bacterial community structure improvement. Citric acid was most effective on improving soil micro-ecology.